KOMUNIKASI PARIWISATA DINAS KEBUDAYAAN DAN PARIWISATA DALAM PENGEMBANGAN “KAMPUNG WISATA OKURA” SEBAGAI DESTINATION BRAN NDING KOTA PEKANBARU - Hidayah Fadillah; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Pekanbaru City has great potential in increasing the tourism sector. This is one of the great assets for the government to develop tourism here. Currently, the Pekanbaru City Culture and Tourism Office has created a tourism development program for this area which aims to brand tourism so that it can become an icon in the region. One of the tourist destinations that is being developed is the Okura Tourism Village. Okura Tourism Village is a village that has culture, natural beauty, and community activities that can be a special attraction for tourists who come to visit. This study aims to determine several stages of destination branding carried out by the Pekanbaru City Culture and Tourism Office in developing the Okura Tourism VillageThis study uses a qualitative method. The research subjects were 6 people. Data collection techniques used are interviews, observation, and documentation. The data analysis technique is by reducing the data, presenting the data, drawing conclusions, and evaluating using the technique of checking the validity of the data, namely triangulation.The results showed that the Pekanbaru City Disbukpar implemented five stages of destination branding in developing the Okura Tourism Village. First, mapping the market potential, namely developing the potential of Malay Culture in Okura Tourism Village and identifying current community trends. Then take advantage of the technological factor, develop a tourist attraction. Second, create a brand identity, namely the name of the tourist destination, Okura Tourism Village. Third, promote through the website, and social media., as well as establishing good relations with the community. Fourth, establish participation with stakeholders, including travel agencies, Pokdarwis, and several hotels. Fifth, monitoring, evaluation, and review, such as monitoring complaints and suggestions from visitors, either directly or through social media, followed by an evaluation process to make improvements to improve the tourism aspect of Okura. keywords: Tourism communication, Tourism Object Development, Destination Branding